Researches of processes of selection of gas bubbles in an oiling environment at running-in and their influence on the change of the mode of friction - Замота, Т.Н.; Аулин, В.В. (Problems of Tribology, 2014)
The results of experimental researches of processes of gassed of electrolyte are resulted at the electrochemical-mechanical at running-in, their influences on tribotechnical descriptions and changes of the modes of friction.